The Effectiveness Of Cross-Sector Coordination in The Implementation of The Integrated Utility Network Policy Of Medan City - Fadli Azhari; Cut Nuraini; Abdi Sugiarto (CV. Doki Course and Training, 2026)
The Integrated Utility Network Facility (SJUT) is a strategic urban policy to reorganize utility infrastructure, improve road-work safety, and enhance urban aesthetics. Yet, its implementation strongly depends on cross-sector coordination involving local government, state-/region-owned enterprises, telecommunication operators, and private partners. This study assesses the effectiveness of cross-sector coordination in Medan's SJUT implementation, identifies key barriers, and proposes coordination-strengthening strategies based on polycentric governance and an integrated utility GIS. A sequential explanatory mixed-methods design was used: a survey (n=100) of stakeholders and corridor users followed by in-depth interviews and policy document review. Findings indicate moderate perceived coordination effectiveness (mean 3.47; SD 0.92), with notable weaknesses in policy awareness/socialization and data-sharing mechanisms. Pearson correlation shows a very strong relationship between coordination and implementation effectiveness (r=0.92; p<0.01). Qualitative evidence highlights three critical issues: the absence of a shared utility map, sectoral ego, and unclear partnership governance (KSO), leading to delays and limited implementation scope. The study recommends establishing a permanent coordination forum, standardizing utility data, and developing an integrated utility GIS as prerequisites for holistic SJUT integration.